2018
DOI: 10.3171/2017.6.spine17288
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on surgical outcomes, narcotics consumption, and hospital costs following anterior cervical discectomy and fusion

Abstract: OBJECTIVEGiven the increasing prevalence of obesity, more patients with a high body mass index (BMI) will require surgical treatment for degenerative spinal disease. In previous investigations of lumbar spine pathology, obesity has been associated with worsened postoperative outcomes and increased costs. However, few studies have examined the association between BMI and postoperative outcomes following anterior cervical discectomy and fusion (ACDF) procedures. Thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Our findings were consistent with the results of Kalanithi et al . but contradicted that of Narain et al …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings were consistent with the results of Kalanithi et al . but contradicted that of Narain et al …”
Section: Discussionsupporting
confidence: 86%
“…All the studies were conducted in the USA, and were published between 2010 and 2018. All the studies were prospective or retrospective cohort studies except one, which was a retrospective cross‐sectional study. Patients in three studies were categorized into the following groups according to their BMI: underweight (<18.5 kg/m 2 ), normal weight (18.5–24.99 kg/m 2 ), overweight (25–29.99 kg/m 2 ), nonobese (18.5–29.9 kg/m 2 ), obese I (30–34.9 kg/m 2 ), obese II (35–39.9 kg/m 2 ), or obese III (≥40 kg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Obesity in all-cause spine surgery increases operative times, EBL, total cost of care, infection rates, and thromboembolism. 17,45 When investigating the impact of obesity in ACDF surgery, specifically more controversy exists. Two studies have demonstrated no difference in functional outcomes, LOS, total cost, and readmission rates following ACDF surgery in obese and nonobese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors previously associated with extended LOS or hospital readmissions include advanced age, gender, race, insurance status, medical comorbidities, preoperative opioid use, preoperative anemia, and multiple-level surgery. [13][14][15][16][17][18][19][20][21][22][23][24][25] The purpose of our study was to identify independent risk factors for extended LOS and 90-day readmission rates following ACDF surgery.…”
Section: Introductionmentioning
confidence: 99%